Emergence of two novel sublineages Ind2001BD1 and Ind2001BD2 of foot‐and‐mouth disease virus serotype O in Bangladesh. Issue 4 (18th February 2018) - Siddique, M. A.; Ali, M. R.; Alam, A. S. M. R. U.; Ullah, H.; Rahman, A.; Chakrabarty, R. P.; Amin, M. A.; Hoque, S. A.; Nandi, S. P.; Sultana, M.; Hossain, M.A.
Summary: Foot‐and‐mouth disease (FMD) is endemic in Bangladesh, and the implementation of a control programme for this disease is at an early stage, according to the FAO‐ and OIE‐proposed Progressive Control Pathway for FMD (PCP‐FMD) Roadmap. To develop an effective control programme, understanding of foot‐and‐mouth disease virus (FMDV) serotypes, even subtypes within the serotypes is essential. The present investigation aims at viral VP1 coding region sequence‐based analysis of FMD samples collected from 34 FMD outbreaks during 2012–2016 in Bangladesh. Foot‐and‐mouth disease virus (FMDV) serotype O was responsible for 82% of the outbreaks in Bangladesh, showing its dominance over serotype A and Asia1. The VP1 phylogeny revealed the emergence of two novel sublineages of serotype O, named as Ind2001BD1 and Ind2001BD2, within the Ind2001 lineage along with the circulation of Ind2001d sublineage in Bangladesh, which was further supported by the multidimensional scaling with distinct clusters for each sublineage. The novel sublineages had evident genetic variability with other established sublineages within Ind2001 lineage. Ten mutations with three or more amino acid variations were detected within B‐C loop, G‐H loop and C‐terminal region of the VP1 protein of FMDV serotype O viruses isolated exclusively from Bangladesh. Furthermore, two amino acid substitutions at positions 197 and 198 within the VP1 C‐terminal region are unique to the novel sublineages. The existence of widespread genetic variations among circulatory FMDV serotype O viruses makes the FMD control programme complex in Bangladesh. Adequate epidemiological data, disease reporting, animal movement control, appropriate vaccination and above all stringent policies of the government are necessary to combat FMD in Bangladesh.